2021
DOI: 10.14719/pst.2021.8.4.1363
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Agrobacterium co-cultivation stage on explant response for subsequent genetic transformation in Soybean (Glycine max (L.) Merr.)

Abstract: The establishment of an efficient in vitro genetic transformation protocol in soybean depends upon an effective interaction between the explants and Agrobacterium tumefaciens. Therefore, a study was conducted at the University of Limpopo, South Africa, between September 2019 and May 2020 to evaluate explant amenability and effects of Agrobacterium co-cultivation stage on the induction of oxidative stress. This stress potentially causes lipid peroxidation, reduction of phytochemicals and chlorophyll pigments on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…1A). Our previous studies indicated that healthy seedlings, typically with smooth and enlarged surfaces suitable for incisions were obtained using MS basal culture medium containing 1.0-4.0 mgL -1 6-BA (Mangena et al, 2017;Mangena, 2021). Furthermore, the use of a double cotyledonary node and inclusion of cytokinins in the medium showed a high regeneration frequency of multiple shoots, even without co-cultivation of explants with Agrobacterium (Dan and Reichert, 1998;Franklin et al, 2004;Kendir et al, 2008).…”
Section: Seed Germination and Cotyledonary Node Explant Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). Our previous studies indicated that healthy seedlings, typically with smooth and enlarged surfaces suitable for incisions were obtained using MS basal culture medium containing 1.0-4.0 mgL -1 6-BA (Mangena et al, 2017;Mangena, 2021). Furthermore, the use of a double cotyledonary node and inclusion of cytokinins in the medium showed a high regeneration frequency of multiple shoots, even without co-cultivation of explants with Agrobacterium (Dan and Reichert, 1998;Franklin et al, 2004;Kendir et al, 2008).…”
Section: Seed Germination and Cotyledonary Node Explant Preparationmentioning
confidence: 99%
“…As such, further physiological and biochemical insights emanating from the interaction of A. tumefaciens with cotyledonary explants are still required to guide and improve the optimization of in vitro and in vivo protocols for soybean transformation. Previous studies showed that the infection of cotyledonary explants with Agrobacterium induced oxidative stress causing physiological changes and metabolic imbalances involving the production of ROS and reduced antioxidant activity, both leading to intense damage of plant cellular structures (Mangena et al, 2017;Mangena, 2021). Further insights are thus, required to ameliorate adverse changes in the metabolic profile and ROS accumulations affecting the proliferation of transformed cells by altering the plant's physiological and defense response mechanisms during soybean transformation (Pitzschke, 2013).…”
Section: Introductionmentioning
confidence: 99%

Advances in Soybean Genetic Improvement

Vargas-Almendra,
Ruiz-Medrano,
Núñez-Muñoz
et al. 2024
Plants